O37 Genital dermatology is a high proportion of the case load presenting to walk-in sexual health services across the united kingdom. (8th June 2017) - Hartley, Anna; Bates, Christine; Fernando, Imali; Basavaraj, Serish; Pritchard, Jillian; Edwards, Sarah; Sethi, Cindy; Goorney, Ben; Vijeratnam, Dayan; Parameswaran, Sashidharan
Abstract : Introduction: Patients with genital dermatology (GD) conditions frequently present to sexual health services. Following service tendering, there are reports of contracts excluding provision of specialist GD services within sexual health. We aimed to review the case load of GD conditions presenting to walk-in sexual health clinics, to reach an understanding of the demand for these services within our specialty. Methods: Members of the BASHH GD Specialist Interest Group collected data on the first 30 to 50 new symptomatic patients presenting to their sexual health walk-in service on 5 th September. Results: 382 patients presented to 9 services across England and Scotland. Of these, 164 (43%) presented with a GD condition. GD STI diagnoses (e.g. warts, herpes simplex) were excluded. 75 patients (20%) presented with non-STI GD conditions. Of these, 59% were male, 91% heterosexual. The modal age range and ethnicity were 18–25 year olds (36%) and white British (67%). GD diagnoses included: candida/tinea 17%, normal variant 11%, eczema 8%, non-specific balanitis 8%, irritant dermatitis 7%, vulvodynia 5%, lichen sclerosus 5%, lichen planus 3%, psoriasis 3%. 17% of cases required senior review. 33% had follow up: 32% by a Genitourinary Medicine consultant; 12% in a Genitourinary Medicine specialist clinic. 4% required skin biopsy. Discussion: Our study demonstrates that non-STI GD conditions constitute a high proportion of clinical presentations to walk-in sexual health services. Many cases require in-house senior input. Commissioners must recognise the burden of GD on services and the expertise required to ensure optimal management of GD within sexual health.